(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In the article, the new constructions of the piled drum and the polygon mesh surface for cleaning cotton from the initial small debris are presented, and the dynamics of interrelationships between the cotton fabric and the polygon surface are theoretically and practically studied.